Integration of the metabolome and transcriptome reveals the molecular mechanism of drought tolerance in Plumeria rubra - Sun, Rong; Liu, Shan; Gao, Jinglei; Zhao, Lihua (Frontiers in Genetics, 2023)
Plumeria rubra L. cv. Acutifolia is an ornamental tree that displays a good drought-tolerance level. However, the molecular mechanisms of P. rubra adaptation to drought stress remains unclear. Here, drought-simulating pot experiments were conducted to explore drought stress response mechanism of P. rubra. Transcriptome analysis revealed 10,967 differentially expressed genes (DEGs), 6,498 of which were increased and 4,469 decreased. Gene Ontology (GO) analysis revealed that the DEGs were enriched in binding category, in metabolic process category, and in catalytic activities category. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that 9 pathways were significantly enriched, including biosynthesis of secondary metabolites (ko01110), plant hormone signal transduction (ko04075) and so on. In addition, the transcription factor families of AP2/ERFs, bZIP, and C2H2 were significantly upregulated while the families of bHLH, MYB-related, and NAC were significantly downregulated. Moreover, the results of metabolomics analysis indicated that some compounds were accumulated under drought stress, especially flavonoids. Overall, it was speculated that under drought stress, P. rubra first activates the plant hormone signal transduction pathway to regulate hormone contents. Then osmotic regulating substances such as organic acids and amino acids are accumulated to maintain osmotic balance. Finally, flavonoid levels are increased to scavenge reactive oxygen species. These results preliminarily revealed the molecular mechanisms adopted by P. rubra in response to drought stress.